THE USE OF AUTHENTIC VIDEO MATERIALS FOR THE FORMATION OF PROJECT ACTIVITY SKILLS IN ENGLISH LESSONS IN SCHOOLS - Gafforov Sanat Ismatovich (Journal of new century innovations, 2023)
Abstract: The article discusses the possibility of using authentic video materials for the formation of project activity skills in English lessons in schools. The classification and requirements for the method of projects are revealed. The possibility of using video materials for the development of listening skills and step- by-step work with them is also being explored.